The Detection of Thyroid Nodules in Prediabetes Population and Analysis of Related Factors - Chang X; Wang Y; Fu S; Tang X; Liu J; Zhao N; Jing G; Niu Q; Ma L; Teng W; Shan Z (Dove Medical Press, 2021)
Xingyu Chang,1,2,* Yaqi Wang,1,2,* Songbo Fu,1,2 Xulei Tang,1,2 Jingfang Liu,1,2 Nan Zhao,1,2 Gaojing Jing,1,2 Qianglong Niu,1,2 Lihua Ma,1,2 Weiping Teng,3 Zhongyan Shan3 1Department of Endocrinology, First Hospital of Lanzhou University, Lanzhou, Gansu, 730000, People's Republic of China; 2Gansu Provincial Endocrine Disease Clinical Medicine Research Center, Gansu, 730000, People's Republic of China; 3Department of Endocrinology, The First Affiliated Hospital of China Medical University, Shenyang, Liaoning Province, 101100, People's Republic of China*These authors contributed equally to this workCorrespondence: Songbo FuDepartment of Endocrinology, First Hospital of Lanzhou University, Lanzhou, Gansu, 730000, People's Republic of ChinaTel +86-13993122257Email fusb@lzu.edu.cnPurpose: To explore the detection of thyroid nodules (TN) and related influencing factors in the population of prediabetes (PreDM) in northwest China's Gansu Province.Materials and Methods: A multi-stage stratified cluster random sampling method was used to select adult Han residents in Gansu Province for investigation, and recorded the clinical data of the subjects. The χ2 test was used to analyze the difference in TN detection rate of the PreDM population. Logistic regression analyzed the risk factors of TN in the PreDM population.Results: This study included 2659 people with normal glucose tolerance (NGT) and PreDM, of which 440 people were detected with TN. Among the PreDM population, the TN detection rate was higher than in the NGT population (24.48% vs 15.00%; P< 0.05). The detection rate of TN in the impaired fasting glucose (IFG), impaired glucose tolerance (IGT) and IFG+IGT group was also significantly higher than that in the NGT population (X2=4.117, X2=13.187, X2=13.016, all P< 0.05), and of which, the IFG+IGT group was the highest (32.20%). The general trend of TN in the IFG, IGT and PreDM population all increased with age. General data showed that BMI, waist-to-height ratio, waist circumference, TG, TC, LDL-C, FPG, 2h PG, HbA1c and TSH indicators in the TN group were higher than those in the Non-TN group (P< 0.05). The logistic regression suggested that the risk factors for TN in the PreDM population were female, age increase, high SP, high TSH, high FPG, high LDL-C, hypertension and family history of diabetes (all P< 0.05).Conclusion: The detection rate of TN in the PreDM population is high, especially in the IFG+IGT population. Middle-aged and elderly people with hypertension and abnormal glucose and lipid metabolism should be treated reasonably and regularly, and their TN should be screened and followed up.Keywords: prediabetes, thyroid nodules, risk factors